İş Yerinde Sosyal Çalışmayı Türkiye İçin Düşünmek. - YANARDAĞ, Umut; ZUBAROĞLU YANARDAĞ, Melek (Çalışma ve Toplum, 2020)
Social work is a profession that help individuals deal with the various difficulties faced in life and increase the well-being of individuals in order to protect their human rights and fulfill their human rights requirements. At first, disadvantaged women, children, disabled people, elderly people and individuals, groups and communities that need to be improved in terms of well-being are beneficiaries of the social work profession. One of the groups that the social work profession is interested in can be noted as workers/employees who face psychosocial problems or work problems and need support. Professional practices for workers and employees in the focus of social work profession are defined as occupational social work. Occupational social work practices are carried out in a lot of countries, but in Turkey occupational social work is poorly understood and not common. In this context, this study aims to reveal the occupational social work practices that developed in the United States and the definition and scope of social work in the workplace (occupational social work), which occurred in parallel with the institutionalization process in US. Also, in this study it is intended to provide examples of how the occupational social work implemented in different countries to discuss implementation of occupational social work practice in Turkey.